Síntese e análise estrutural de clusters derivados de bis(fenilseleneto) de cádmio Cd(SePh)2 - Stieler, Rafael (2009)
This work deals with the synthesis and structural analysis of clusters derivative from cadmium bis(phenylselenolate) - Cd(SePh)2. The methodology for the synthesis was based on the use of Cd(SePh)2 as a starting material, as well as in the in situ generation of the chemical intermediary PhSeCdX (X = Cl, Br, I). These compounds are considered basic building blocks for the synthesized clusters. Through solvothermal conditions and the use of different kinds of phosphine ligands, five new cadmium clusters were obtained. The compounds synthesized were: [Cd4(SePh)7(PPh3)Cl]n (1), [Cd4(SePh)7(PPh3)Br]n (2), [Cd(SePh)(PCy3)Br]2 (3), [Cd(SePh)(PCy3)I]2 (4) and [Cd4(SePh)7(PCy3)Br]n (5). A structural study in the solid state of these compounds was carried out using the X-ray diffraction on single crystal method. All compounds were characterized by elemental analysis, infrared spectroscopy and energy dispersive X-ray spectroscopy.